Digital Economic Transformation In Developing Countries: Analysis Of The Impact Of Artificial Intelligence Adoption On Productivity, Inequality, And Market Structure - Gabriella (Journal of Global Economic Development and Policy, 2025)
This study investigates the transformative role of artificial intelligence (AI) in shaping economic performance and structural dynamics within developing countries, focusing on three interrelated outcomes: productivity, inequality, and market structure. As AI becomes a general-purpose technology with wide-ranging economic applications, its diffusion in emerging markets presents both substantial opportunities and significant systemic risks. Building on recent empirical evidence, the study examines how AI adoption enhances firm-level efficiency, operational precision, and innovation capacity while evaluating the extent to which these micro-level gains translate into aggregate productivity improvements. The analysis also addresses distributional consequences, emphasizing how unequal access to digital infrastructure, skills, and capital may deepen existing socioeconomic disparities. Moreover, the study explores the implications of AI-driven platformization and data concentration for market competitiveness, particularly in economies characterized by regulatory gaps and high informality. By integrating insights from development economics, digital-technology studies, and industrial-organization theory, this research provides a comprehensive framework for assessing AI’s multidimensional impact on developing countries. The findings aim to guide policymakers in designing inclusive digital-transformation strategies that maximize productivity gains, mitigate inequality, and preserve competitive market environments in the era of advanced automation.